KONSUMSI DAN KECERNAAN JERAMI JAGUNG MANADO KUNING DAN JERAMI JAGUNG HIBRIDA JAYA 3 PADA SAPI PO - Tuwaidan, Nancy W.H.; Waani, M. R.; -, Rustandi -; Malalantang, S. S. (ZOOTEC, 2015)
ABSTRACT INTAKE AND DIGESTIBILITY OF YELLOW MANADO AND JAYA 3 HYBRID CORN SRAWS FOR ONGOLE GRADE CATTLE. Experiment was conducted to determine the intake capacity and digestibility of Manado yellow corn straw (MYCS) and Jaya 3 hybrid corn straw (J3HCS) as single feed for Ongole grade cattle (OGC). Five female OGC were used in this experiment, applied into two periods. The animals were fed with MYCS in the first stage and J3HCS in the second stage. The measured variables were including dry matter intake (DMI), dry matter digestibility (DMD), digestibility of crude protein (DCP) and digestibility of Neutral Detergent Fiber (DNDF). The data were analyzed by T test. The results showed that treatment significantly affected (p <0.05) the DMI, DMD, DCP and DNDF. It can be concluded DMI, DMD, DCP and DNDF of MYCS were higher than those of J3HCS. Â  Key words: Dry matter Intake, Digestibility, Corn straw, Ongole grade cattle. Â